2018
DOI: 10.1016/j.aju.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary use of ultrasonic versus standard electrosurgical dissection in laparoscopic nephrectomy: Safety, efficacy and cost

Abstract: ObjectiveTo assess the safety, efficacy and cost-effectiveness of ultrasonic dissection (USD) compared with standard monopolar electrosurgery (ES) in laparoscopic nephrectomy (LN).Patients and methodsRetrospective analysis of patients’ records who underwent elective LN was performed. Patients were divided in to two groups: USD and ES groups depending on the energy source used during LN. The preoperative (demographics, indication for surgery), intraoperative (conversion to open surgery, operative time, estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Modern surgical treatments such as laparotomy, laparoscopic surgery, and robotic surgery have become safer due to medical devices improvement. Especially, introduction of surgical energy devices such as electrical scalpel and ultrasonically activated scalpel improved the surgical treatment operation [1,2,3,4,5,6]. Surgical energy devices are capable of coagulating the biological tissue, blood vessel sealing, and cutting the biological tissue, resulting in a new treatment that enables both hemostasis and incision with a single device.…”
Section: Introductionmentioning
confidence: 99%
“…Modern surgical treatments such as laparotomy, laparoscopic surgery, and robotic surgery have become safer due to medical devices improvement. Especially, introduction of surgical energy devices such as electrical scalpel and ultrasonically activated scalpel improved the surgical treatment operation [1,2,3,4,5,6]. Surgical energy devices are capable of coagulating the biological tissue, blood vessel sealing, and cutting the biological tissue, resulting in a new treatment that enables both hemostasis and incision with a single device.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical devices such as an electrical scalpel and ultrasonically activated scalpel are currently used modern surgery [1]- [6]. However, it is reported that these devices generate surgical smoke during coagulating and incision of biological tissues, which has become a problem.…”
Section: Introductionmentioning
confidence: 99%
“…In modern surgery, surgical devices having multiple functions (e.g., tissue coagulation and tissue resection) are frequently used [1,2,3,4]. These devices contribute to shortening the operation time and suppressing the amount of bleeding [5,6].…”
Section: Introductionmentioning
confidence: 99%